Combined Ventilation of Two Subjects with a Single Mechanical Ventilator Using a New Medical Device: An In Vitro Study - Ignacio Lugones; Matías Ramos; María Fernanda Biancolini; Roberto Orofino Giambastiani (Anesthesiology Research and Practice)
Introduction. The SARS-CoV-2 pandemic has created a sudden lack of ventilators. DuplicARⓇ is a novel device that allows simultaneous and independent ventilation of two subjects with a single ventilator. The aims of this study are (a) to determine the efficacy of DuplicARⓇ to independently regulate the peak and positive-end expiratory pressures in each subject, both under pressure-controlled ventilation and volume-controlled ventilation and (b) to determine the ventilation mode in which DuplicARⓇ presents the best performance and safety. Materials and Methods. Two test lungs are connected to a single ventilator using DuplicARⓇ. Three experimental stages are established: (1) two identical subjects, (2) two subjects with the same weight but different lung compliance, and (3) two subjects with different weights and lung compliances. In each stage, the test lungs are ventilated in two ventilation modes. The positive-end expiratory pressure requirements are increased successively in one of the subjects. The goal is to achieve a tidal volume of 7 ml/kg for each subject in all different stages through manipulation of the ventilator and the DuplicARⓇ controllers. Results. DuplicARⓇ allows adequate ventilation of two subjects with different weights and/or lung compliances and/or PEEP requirements. This is achieved by adjusting the total tidal volume for both subjects (in volume-controlled ventilation) or the highest peak pressure needed (in pressure-controlled ventilation) along with the basal positive-end expiratory pressure on the ventilator and simultaneously manipulating the DuplicARⓇ controllers to decrease the tidal volume or the peak pressure in the subject that needs less and/or to increase the positive-end expiratory pressure in the subject that needs more. While ventilatory goals can be achieved in any of the ventilation modes, DuplicARⓇ performs better in pressure-controlled ventilation, as changes experienced in the variables of one subject do not modify the other one. Conclusions. DuplicARⓇ is an effective tool to manage the peak inspiratory pressure and the positive-end expiratory pressure independently in two subjects connected to a single ventilator. The driving pressure can be adjusted to meet the requirements of subjects with different weights and lung compliances. Pressure-controlled ventilation has advantages over volume-controlled ventilation and is therefore the recommended ventilation mode.